QSAR in Flavonoids by Similarity Cluster Prediction - M. Harsa, Alexandra; E. Harsa, Teodora; D. Bolboaca, Sorana; V. Diudea, Mircea (Current Computer - Aided Drug Design, 2014)
Quantitative Structure-Activity Relationships based on molecular descriptors calculated with correlation weights within the hypermolecule, considered to mimic the investigated correlational space, was performed on a set of 40 flavonoids (PubChem database). The best models describing log P and LD50 of this set of flavonoids were validated by the leave-one-out procedure, in the external test set and in a new version of prediction by using clusters of similar molecules. The best prediction was provided by the similarity cluster procedure.
Keywords: log P